How to think about weird things : critical thinking for a new age - Schick, Theodore; Vaughn, Lewis (Dubuque, IA : McGraw-Hill, 2010)
"This brief, affordable text helps students to think critically, using examples from the weird claims and beliefs that abound in our culture to demonstrate the sound evaluation of any claim. It explains step-by-step how to sort through reasons, evaluate evidence, and tell when a claim (no matter how strange) is likely to be true. The emphasis is neither on debunking nor on advocating specific assertions, but on explaining principles of critical thinking that enable readers to evaluate claims for themselves. The authors focus on types of logical arguments and proofs, making How to Think about Weird Things a versatile supplement for logic, critical thinking, philosophy of science, or any other science appreciation courses."--pub. desc.
Includes bibliographical references and index.
Keywords: Critical thinking; Curiosities and wonders